2017
DOI: 10.1371/journal.pone.0189411
|View full text |Cite
|
Sign up to set email alerts
|

Optimized maritime emergency resource allocation under dynamic demand

Abstract: Emergency resource is important for people evacuation and property rescue when accident occurs. The relief efforts could be promoted by a reasonable emergency resource allocation schedule in advance. As the marine environment is complicated and changeful, the place, type, severity of maritime accident is uncertain and stochastic, bringing about dynamic demand of emergency resource. Considering dynamic demand, how to make a reasonable emergency resource allocation schedule is challenging. The key problem is to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In the current study, we retrospectively retrieved data on the water traffic volume between 2008 and 2019 and divided it into the annual water passenger volume, annual water freight volume, annual number of transportation ships, annual total ship carrying capacity, annual number of persons in distress, annual number of ship accidents, SAR success rate, and dispatched SAR forces and were analyzed statistically. We found an increase in water traffic volume and ship carrying capacity, but a reduction in the number of (20)(21)(22). As soon as a request for help is received, SAR workers are immediately contacted by the CMSRC via the coordination of professional rescue ships operated by government or social welfare organization, military ships, nearby fishing ships, passing ships, and/or helicopters to rescue the ships and persons in distress (19)(20)(21).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…In the current study, we retrospectively retrieved data on the water traffic volume between 2008 and 2019 and divided it into the annual water passenger volume, annual water freight volume, annual number of transportation ships, annual total ship carrying capacity, annual number of persons in distress, annual number of ship accidents, SAR success rate, and dispatched SAR forces and were analyzed statistically. We found an increase in water traffic volume and ship carrying capacity, but a reduction in the number of (20)(21)(22). As soon as a request for help is received, SAR workers are immediately contacted by the CMSRC via the coordination of professional rescue ships operated by government or social welfare organization, military ships, nearby fishing ships, passing ships, and/or helicopters to rescue the ships and persons in distress (19)(20)(21).…”
Section: Discussionmentioning
confidence: 76%
“…To ensure that the SAR commands and coordination instructions are promptly and rapidly implemented and executed, by the end of 2021, the CMSRC has established 14 branches along the approximately 18,000 km of Chinese coastline and the Yangtze River Main Line (20). Additionally, a series of regulations and laws have been formulated and applied by the CMSRC, such as the law of the People's Republic of China on Maritime Traffic Safety, National Maritime Search and Rescue Regulations, and National Maritime Search and Rescue Emergency Plan (20)(21)(22). Our current study revealed a reduction in the number of deaths caused by distress, ship collisions, and ship collisionrelated accidents, although there was an increase in water traffic volume and ship carrying capacity without significant changes in the locations and causes of annual ship accidents or the success rate between 2008 and 2019.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarhadi et al (2020) present a robust optimization approach to the problem of designing emergency response networks for marine oil spills given uncertainty in the location, size and type of the spill. Zhang et al (2017b) propose a maritime emergency resource allocation model with a robust approach to deal with the uncertainty of location, type and severity of oil spills. However, the research on post-disaster maritime emergency logistics is still in preliminary exploration.…”
Section: Introductionmentioning
confidence: 99%